Targeted ablation of beta cells in the embryonic zebrafish pancreas using E.coli nitroreductase - Pisharath, Harshan (2006)
In order to generate a zebrafish model of β cell regeneration, we have expressed an E.coli gene called nfsB in the β cells of embryonic zebrafish. This bacterial gene encodes a nitroreductase (NTR) enzyme, which can convert prodrugs such as metronidazole (Met) to cytotoxins. By fusing nfsB to mCherry, we can simultaneously render β cells susceptible to prodrug and visualize Met dependent cell ablation. We show that the neighboring α and δ cells are unaffected by prodrug treatment and that ablation is β cell specific. Following drug removal and 36hrs of recovery, β cells regenerate. Using ptf1a morphants, it is clear that this β cell recovery occurs independently of the presence of the exocrine pancreas. Also, by using photoconvertible Kaede to cell lineage trace and BrdU incorporation to label proliferation, we investigate mechanisms for β regeneration. Therefore, we have developed a unique resource for the study of β cell regeneration in a living vertebrate organism, which will provide the opportunity to conduct large-scale screens for pharmacological and genetic modifiers of β cell regeneration.